Diversity and Relative Abundance of Insect Pollinators in Moroccan Agroecosystems - El Abdouni, Insafe; Lhomme, Patrick; Christmann, Stefanie; Dorchin, Achik; Sentil, Ahlam; Pauly, Alain; Hamroud, Laila; Ihsane, Oumayma; Reverté, Sara; Patiny, Sebastien; Wood, Thomas J.; Bencharki, Youssef; et al. (Frontiers in Ecology and Evolution, 2022)
Agroecosystems are often impoverished ecosystems, but they can host diverse communities of insects which provide ecosystem services. Specifically, crops may benefit from insect pollinators that increase their quantity and quality of yields. Basic knowledge is still needed regarding the identity, diversity, abundance, and ecology of insect pollinators in many parts of the world, especially in low and middle-income countries. In this study we investigate the potential of agroecosystems and crops in Morocco to host a high diversity of insect pollinators. We sampled insects in four eco-climatic regions encompassing a total of 22 crops for two years (2018-2019). After describing the general pattern of diversity and abundance of insect pollinators, we focused our comparative analyses on bees as they are known to be the most efficient and abundant group of insect pollinators. We recorded a total of 53,361 insect pollinators in all agroecosystems among which 37,091 were visiting crop flowers. Bees were by far the most abundant group visiting crops. Honeybees represented 49% of crop visitors followed by wild bees representing 33% of relative abundance. Three genera (Lasioglossum, Andrena and Xylocopa) represented 53% of the total abundance of wild bees visiting crops. We identified a total of 213 species visiting crops (22% of national wild bee species richness). A comparison of the abundance, species richness, and community composition of wild bees visiting the same crops showed significant inter-regional differences for zucchini, faba bean, and eggplant. This study highlights the high diversity of pollinators in Moroccan agroecosystems and represents an important step towards exploring the Moroccan pollinator fauna. It provides basic information for future studies on pollinator conservation and pollination services.